Public policies and women's employment after childbearing - Wen-Jui Han; Christopher J. Ruhm; Jane Waldfogel; Elizabeth Washbrook (Institute for the Study of Labor (IZA), 2009)
This paper examines how the public policy environment in the United States affects work by new mothers following childbirth. We examine four types of policies that vary across states and affect the budget constraint in different ways. The policy environment has important effects, particularly for less advantaged mothers. There is a potential conflict between policies aiming to increase maternal employment and those maximizing the choices available to families with young children. However, this tradeoff is not absolute since some choice-increasing policies (generous child care subsidies and state parental leave laws) foster both choice and higher levels of employment.
urn:nbn:de:101:1-2009020973
Keywords: J13; J18; J22; 330; Public policies; maternal employment; childbearing; Familienpolitik; Mütter; Frauenerwerbstätigkeit; Berufliche Integration; USA